Political Activity of Revolution Leaders and Masses in Russian Province - Viktorovna, Simonova Elena (Journal of History Culture and Art Research, 2017)
The article is dedicated to a complicated question concerned the role of party leaders in revolution propaganda in Russian provinces in 1917. The author observes different kinds of political mind during the revolution and activity of different groups of people in revolution events. The main role in arranging and strengthening the local revolutionary organizations played the party leaders of the central party organizations who visited provinces for a special purpose or transiently during the transit under the police supervision. But sometimes it was hard for them to rule the masses because of their political unconsciousness.